Local Government Challenges in post apartheid South Africa - (:unkn) unknown (My University, 2002)
The restructuring of local government is especially significant in the context of South Africa's emerging democracy, especially since this transformation "has taken place in a way that is probably unique from an international comparative perspective". Out of all the political systems that have gone through a non-revolutionary regime transition from authoritarianism to democracy, South Africa is the only one where this transition occurred simultaneously at a national and sub-national level. The reasons for this relate to a large extent to the structure of South Africa's towns and cities and to the nature of the urban social movements that resisted, challenged and overthrew urban apartheid during the decade of defiance that led up to the decade of transition, namely the 1980s" (Swilling, Monteiro and Johnson, 1995:16, original emphasis).
Keywords: African Research